2001
DOI: 10.1266/ggs.76.25
|View full text |Cite
|
Sign up to set email alerts
|

The maternal origins of the triploid ginbuna(Carassius auratus langsdorfi): Phylogenetic relationships within the C. auratus taxa by partial mitochondrial D-loop sequencing.

Abstract: The hyper-variable segments (323~327 bp) of the mitochondrial D-loop for 169 Carassius auratus fishes in Japan were amplified by the polymerase chain reaction and the amplified products were sequenced directly and compared. A dendrogram showing three major clusters was generated with the sequence data for 37 haplotypes at 66 polymorphic sites. One cluster (cluster I) exclusively consisted of the gengorobuna, which was regarded as an independent (sub) species. The triploid ginbuna belonged to two remaining clus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
50
1
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(57 citation statements)
references
References 17 publications
(18 reference statements)
4
50
1
2
Order By: Relevance
“…Several other researches also failed to find an evidence for a complete genetic separation between triploids and diploids, leading the authors to suggest multiple origins of triploid form or a genetic exchange between the two forms (Murakami et al 2001;Brykov et al 2005;Apalikova et al 2008). Interconversion of diploid and triploid forms has been reported in L. alburnoides (Alves et al 2001), while Schories et al (2007) found no variability between mtDNA sequences of diploid and triploid P. formosa forms.…”
Section: Genetic Divergence Between Diploids and Triploidsmentioning
confidence: 97%
“…Several other researches also failed to find an evidence for a complete genetic separation between triploids and diploids, leading the authors to suggest multiple origins of triploid form or a genetic exchange between the two forms (Murakami et al 2001;Brykov et al 2005;Apalikova et al 2008). Interconversion of diploid and triploid forms has been reported in L. alburnoides (Alves et al 2001), while Schories et al (2007) found no variability between mtDNA sequences of diploid and triploid P. formosa forms.…”
Section: Genetic Divergence Between Diploids and Triploidsmentioning
confidence: 97%
“…auratus gibelio 两个亚种, 两者的分布区域大体上 以长城为界 (Chen & Huang, 1982;Ren et al, 2002;Shen et al, 1997) (Chen & Huang, 1982;Ren et al, 2002;Shen et al, 1997) (Chen & Huang, 1982;Ren et al, 2002), 但《中国动物志·硬骨鱼纲·鲤形目·下卷》中记 载其鳃耙数为 30~52 (Luo & Yue, 2000)。这可能是 排版疏忽造成的, 因为该书的前期工作总结形成的 《中国鲤科鱼类志》中记载其鳃耙数为 27~29 (Chen & Huang, 1982)。白鲫 (C. cuveri)分布范围较窄只 限于日本列岛的部分水域, 该种鳃耙密而细长, 数 目为 92~130, 据此特征可以与鲫属其他种或亚种区 分 (Hosoya, 2002)。鲫(C. auratus)在东亚有广泛的地 理分布 (Chen & Huang, 1982;Hosoya, 2002;Ren et al, 2002;Shen et al, 1997), 近年来更入侵到中亚和 欧洲的部分水体中 (Jakovlić & Gui, 2011;Kalous et al, 2007;Tsoumani et al, 2006;Wheeler, 2000), 其生 物学特性复杂,分类也最不完善。 (Gui, 2007;Gui & Zhou 2010), 有学者在研 究中习惯将三倍体等同于银鲫 (Gui, 2007;Shen et al, 1997)。近年来日本学者也习惯将日本分布的多倍 体鲫归为关东鲫(C. auratus langsdorfii) (Hosoya, 2002;Ohara et al, 1999Ohara et al, , 2000, 但是越来越多的研 究发现三倍体鲫在线粒体谱系上更加接近于同域 的二倍体 (Apalikova et al, 2008;Brykov et al, 2002;Murakami et al, 2001;Takada et al, 2010 …”
Section: 鲫属(Carassius)。 余下的unclassified
“…2、 C. auratus grandoculis、 C. auratus buergeri 和 C. auratus. langsdorfii (Hosoya, 2002)。 白鲫 (C. cuvieri)早期被认为是鲫 (C. auratus)的一 个亚种, 后来由于分子证据支持了其单系性, 被认 定为一个独立的种 (Murakami et al, 2001)。 由于鲫属鱼类的地理分布广, 表型变异大, 染 色体倍性和生殖方式复杂, 其分类一直没有得到很 好的解决 (Ren et al, 2002;Takada et al, 2010)。例如, 由于中国和日本的雌核发育多倍体鲫鱼最初分别 是在银鲫 (C. auratus gibelio) (Gui, 2007;Shen et al, 1997)和关东鲫 (C. auratus langsdorfii) (Kobayasi, 1971;Kobayasi et al, 1970)中发现的, 后来学者们习 惯上将中国和日本的雌核发育多倍体鲫鱼分别视 为 银 鲫 (Gui, 2007;Shen et al, 1997) 和 关 东 鲫 (Hosoya, 2002;Ohara et al, 1999Ohara et al, , 2000。但是近年的 研究发现多倍体在遗传上可能更接近同域的二倍 体 而 不 是 异 域 的 多 倍 体 (Apalikova et al, 2008;Brykov et al, 2002;Murakami et al, 2001;Takada et al, 2010), 将银鲫和关东鲫等同于多倍体的观点值得 商榷;而且即使将银鲫和关东鲫等同于雌核发育多 倍体, 中国多倍体与日本多倍体间的关系也有待厘 正。又如,虽然日本的 C. auratus 鉴定作为 5 个亚 种, 但是这些亚种似乎并不是单系群(monophyletic group) Yamamoto et al, 2010)。我 国 学 者 倾 向 将 银 鲫 视 为 鲫 的 一 个 亚 种 (Chen & Huang, 1982;Luo & Yue, 2000), 然而,近年来国外 学者更多的是将其视为一个有效种 (Halacka et al, 2003;Liousia et al, 2008;Öezuluğ et al, 2004)。鲫属 鱼类, 特别是鲫(C. auratus auratus)指名亚种和银 鲫(C. auratus gibelio)亚种的形态鉴别较为困难。本 文取样时,严格按照《中国鲤科鱼类志》 (Chen & Huang, 1982)、 《中国动物志•硬骨鱼纲· 鲤形目· 下 卷》) (Luo & Yue, 2000)的检索标准加以甄别。 加拿大 Guelph 大学的 Hebert 教授于 2003 年首 次提出通过对一个标准基因的 DNA 序列分析, 作 为一种新的物种鉴定手段,即 DNA 条形码 (Hebert et al, 2003a)。许多研究已经证实了线粒体细胞色素 c 氧化酶亚基 I(cytochrome c oxidase subunit I, COI) 靠近 5′端的一段约 650 bp 序列作为 DNA 条码识别 鱼类物种的有效性 (Ward et al, 2005(Ward et al, , 2008(Ward et al, , 2009 (Komiyama et al, 2009)。银鲫(C. auratus gibelio)主要分布于长城以北, 我国鱼类遗传学者习 惯上将其等同于雌核发育多倍体鲫鱼。金鱼是有性 生殖二倍体, 历史文献记载应起源于南宋时期杭州 一带 (Chen, 1959;Wang, 2007 C. carassius AB379915-AB379921 sequences which were submitted by …”
unclassified
“…Individuals within each lineage are morphologically similar yet their chromosome numbers and reproductive strategies vary. Except for exclusively tetraploid C. cuvieri, bisexual tetraploid and gynogenetic hexaploid and occasional octaploid forms occur sympatrically in China, Russia and Japan (Golovinskaya et al, 1965;Chen et al, 1996;Murakami et al, 2001;Brykov et al, 2002). Multiple levels of polyploidy occur in Fangzheng, Puan and Lake Dianchi, China (Zan, 1982;Zan et al, 1986 and therein;Chen et al, 1996 and therein).…”
Section: Introductionmentioning
confidence: 99%